Opto-electric investigation for Si/organic heterojunction single-nanowire solar cells. Issue 1 (December 2017) - Yang, Zhenhai; Liu, Zhaolang; Sheng, Jiang; Guo, Wei; Zeng, Yuheng; Gao, Pingqi; Ye, Jichun
Abstract Recently, silicon single nanowire solar cells (SNSCs) serving as the sustainable self-power sources have been integrated into optoelectronic nanodevices under the driver of technology and economy. However, conventional SNSC cannot provide the minimum energy consumption for the operation of nanodevices due to its low power conversion efficiency (PCE). Here, we propose an innovative approach to combine then -type silicon nanowires (SiNWs) withp -type poly(3, 4-ethylthiophene):poly(styrenesulfonate) (PEDOT:PSS) to form thep + n heterojunction, which shows superior opto-electric performances. Besides, PEDOT:PSS also acts as a natural anti-reflection coating (ARC) with an excellent light-trapping capability, especially in the short-wavelength range. Importantly, the photovoltaic performances of Si/PEDOT:PSS SNSC can be well maintained even in large surface recombination velocity, due to the efficient field-effect passivation of PEDOT:PSS. The minority carrier concentration at outer surface of shallowp + n heterojunction is greatly reduced by the electric field, drastically suppressing the surface recombination compared to the conventionalp-i-n homojunction SNSC. Furthermore, larger junction area ofp + n heterojunction facilitates the separation of photo-generated charge carriers. These results demonstrate that the Si/PEDOT:PSS SNSC is a promising alternative for micro power application.